PENGELOLAAN FASILITAS DI MUSEUM SANG NILA UTAMA PROVINSI RIAU - Fuad Akbar; Andi M Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research aim to find how the management of facility at he Museum Sang Nila Utama of Riau Province.This research use qualitative methods with deskriptip by explain actuallly situation by displaying collect the data and information by interview, observation and documentacion.Based on the result of the research that has been done, the management of facility at the Museum Sang Nila Utama of Riau Province are stil less well, beacause some aspects. The Museum San g Nila Utama must do maintenace and repairing some aspects in The Museum Sang Nila Utama of Riau Province.Key word : Management, Facility, The Museum Sang Nila Utama